# Solve $2x-2yd=y+xd$ for $d$

Solve for $d$

$$2x-2yd=y+xd$$ $$2(x-yd)=y+xd$$ $$2(x-yd)-y=xd$$ $$\frac{2(x-yd)-y}{x}=d$$ Now I think this is wrong considering I have a $d$ on the other side and I would have to reverse my work and end up at the beginning. Any small pointers or tips? Thanks!

-
Group all the terms with $d$ in them on one side, and everything else on the other. Factor out the $d$... – The Chaz 2.0 Jul 16 '12 at 4:59
Is it; $\dfrac{2x-y}{x-2y}=d$ ??? – Austin Broussard Jul 16 '12 at 5:03
$\dfrac{2x-y}{x + 2y} = d$, if I'm not mistaken – The Chaz 2.0 Jul 16 '12 at 5:07
Oh, right. I wrote the OP wrong in my notebook. Thanks a lot. This was easier than I made it out to be! – Austin Broussard Jul 16 '12 at 5:07
You might consider writing up your work in an answer. Then you can accept your own answer (seems funny, doesn't it!) to indicate that this problem is solved. – The Chaz 2.0 Jul 16 '12 at 5:10

$$2x−2yd=y+xd$$ $$2x - y = 2yd + xd$$ $$2x - y = d(2y + x)$$ $$\dfrac{2x-y}{2y+x} = d$$